Identifying student needs in english for information technology at the post-secondary level - Diyar Nurmetov; Siswantoyo Siswantoyo; Nataša Bakić-Mirić; Asel Chaklikova (Jurnal Cakrawala Pendidikan, 2023)
Mastering English language skills has been indispensable in every sphere of life and in every profession, and Information Technology (IT) as a field is no exception as it perpetually develops and changes. This is a survey study aiming at identifying English language needs of IT specialists working both domestically and abroad, by involving 85 alumni form three Kazakhstani IT institutes. The data were collected through a needs analysis questionnaire for post-secondary level ESP course and were analysed through descriptive percentages. The results of the study revealed that reading, listening, and speaking were the most essential skills for IT professionals for successful performance at work. Reading technical documentations and professional blogs aids specialists in solving common challenges in their industry, whereas listening and watching professionally oriented videos increases their qualification. Additionally, the study implies that there may have been a mismatch between university-level ESP curricula and professional English language proficiency.